Association between short-term exposure to ambient air pollution and heart failure: An updated systematic review and meta-analysis of more than 7 million participants - Yu-shan Yang; Yu-shan Yang; Ying-hao Pei; Yuan-yuan Gu; Yuan-yuan Gu; Jun-feng Zhu; Jun-feng Zhu; Peng Yu; Xiao-hu Chen (Frontiers Media S.A., 2023)
IntroductionExposure to air pollution has been linked to the mortality of heart failure. In this study, we sought to update the existing systematic review and meta-analysis, published in 2013, to further assess the association between air pollution and acute decompensated heart failure, including hospitalization and heart failure mortality.MethodsPubMed, Web of Science, EMBASE, and OVID databases were systematically searched till April 2022. We enrolled the studies regarding air pollution exposure and heart failure and extracted the original data to combine and obtain an overall risk estimate for each pollutant.ResultsWe analyzed 51 studies and 7,555,442 patients. Our results indicated that heart failure hospitalization or death was associated with increases in carbon monoxide (3.46% per 1 part per million; 95% CI 1.0233-1.046, P < 0.001), sulfur dioxide (2.20% per 10 parts per billion; 95% CI 1.0106-1.0335, P < 0.001), nitrogen dioxide (2.07% per 10 parts per billion; 95% CI 1.0106-1.0335, P < 0.001), and ozone (0.95% per 10 parts per billion; 95% CI 1.0024-1.0166, P < 0.001) concentrations. Increases in particulate matter concentration were related to heart failure hospitalization or death (PM2.5 1.29% per 10 μg/m3, 95% CI 1.0093-1.0165, P < 0.001; PM10 1.30% per 10 μg/m3, 95% CI 1.0102-1.0157, P < 0.001).ConclusionThe increase in the concentration of all pollutants, including gases (carbon monoxide, sulfur dioxide, nitrogen dioxide, ozone) and particulate matter [(PM2.5), (PM10)], is positively correlated with hospitalization rates and mortality of heart failure.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021256241.